Synthesis and Antimycobacterial Activity of Thiazole Derivatives - Part-VI - USHA RANI, P.; CHANDRA SEKHAR, B.V.V.N.; RAMESH KUMAR, N.; MUKKANTI, K.; R. SHIRADKAR, MAHENDRA; CHAKRAVARTHY AKULA, KALYAN (Asian Journal of Chemistry, 2010)
Tuberculosis is alarming due to multi drug resistance. Inhibition of an enzyme RmlC by the thiazole derivatives especially with carbonyl group scaffold has prompted us to synthesize a series of thiazole derivatives. Here the work done is presented and antimicrobial and antimycobacterial activities are discussed. Many of these compounds have shown better antimicrobial and antimycobacterial activities while others were inactive.